Inflammation-induced pain sensitization in men and women: does sex matter in experimental endotoxemia?. Issue 10 (October 2015) - Wegner, Alexander; Elsenbruch, Sigrid; Rebernik, Laura; Roderigo, Till; Engelbrecht, Elisa; Jäger, Marcus; Engler, Harald; Schedlowski, Manfred; Benson, Sven
Abstract : Abstract: A role of the innate immune system is increasingly recognized as a mechanism contributing to pain sensitization. Experimental administration of the bacterial endotoxin lipopolysaccharide (LPS) constitutes a model to study inflammation-induced pain sensitization, but all existing human evidence comes from male participants. We assessed visceral and musculoskeletal pain sensitivity after low-dose LPS administration in healthy men and women to test the hypothesis that women show greater LPS-induced hyperalgesia compared with men. In this randomized, double-blind, placebo-controlled crossover study, healthy men (n = 20) and healthy women using oral contraceptives (n = 20) received an intravenous injection of 0.4 ng/kg body weight LPS or placebo. Pain sensitivity was assessed with established visceral and musculoskeletal pain models (ie, rectal pain thresholds; pressure pain thresholds for different muscle groups), together with a heartbeat perception (interoceptive accuracy) task. Plasma cytokines (tumor necrosis factor-α and interleukin-6) were measured along with state anxiety at baseline and up to 6-hour postinjection. Lipopolysaccharide application led to significant increases in plasma cytokines and state anxiety and decreased interoceptive awareness in men and women ( P < 0.001, condition effects), with more pronounced LPS-induced cytokine increases in women ( P < 0.05, interaction effects). Although both rectal and pressure pain thresholds were significantly decreased in the LPS condition (all P < 0.05, condition effect), no sex differences in endotoxin-induced sensitization were observed. In summary, LPS-induced systemic immune activation leads to visceral and musculoskeletal hyperalgesia, irrespective of biological sex. These findings support the broad applicability of experimental endotoxin administration as a translational preclinical model of inflammation-induced pain sensitization in both sexes. Abstract : Endotoxin-induced systemic immune activation leads to visceral and musculoskeletal hyperalgesia in healthy humans, irrespective of biological sex.